MitsuDomoe: Ecosystem Simulation of Virtual Creatures in Petri Dish Display - Ohshima, Toshikazu; Kojima, Kenzo (International Journal of Virtual Reality, 2017)
In this study, we propose the use of mixed reality (MR) for the purposes of biological education. Our objective is to create an interactive edutainment MR framework for users to learn about nature and human beings. MitsuDomoe, an interactive ecosystem simulator of virtual creatures in a petri dish, comprises three species of primitive artificial creatures. MitsuDomoe simulates the predation chain of the virtual creatures in the petri dish, and users can interact with this ecosystem via the petri dish interface. Users can also experience immersive observation by wearing HMD. By combining the MR petri dish and immersive virtual reality (VR) interfaces, we synergistically improve user understanding of the experience.